Mapping Islamic education curriculum research (1981–2024): A bibliometric analysis of trends, authorship, and themes - Aryadi, Ikhsan; Lismawati, Lismawati; Aisyah, Nurul (Asatiza: Jurnal Pendidikan, 2025)
This study examines the development and trends in Islamic education curriculum research from 1981 to 2024. Data were extracted from Scopus on November 7, 2024, using the query TITLE-ABS-KEY (Curriculum and Islamic and Education). After excluding non-English documents and non-article publications, 418 articles were analyzed bibliometrically. The analysis employed RStudio for statistical processing, VOSviewer for network visualization (co-authorship and keyword co-occurrence), and Microsoft Excel for supplementary data management. Findings indicate that Arvisais, O., Sanjakdar, F., and Zulfikar, T. were the most prolific authors (4 publications each). Ar-Raniry State Islamic University emerged as the leading institution (11 articles), while Indonesia contributed the highest output (162 articles). The Journal of Islamic Education published the most relevant studies (17 articles). This study provides a systematic overview of the field and suggests future research explore comparative curriculum models in Muslim-majority versus minority contexts.